2009
DOI: 10.1021/je900248a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature, Composition, and Shear Rate on Polyvinylidene Fluoride/Dimethylacetamide Solution Viscosity

Abstract: Viscosity required for casting or spinning dope polymeric solution plays an essential role in the formulation of flat sheets and hollow fiber membranes. A flat sheet membrane can be casted from a polymer dope with viscosity as low as a few hundred centipoises; by contrast, a few thousand are required to spin polymeric hollow fibers. In this study, an empirical correlation describing the effect of temperature, polymer mass fraction, and shear rates on the viscosity of polyvinylidene fluoride polymer in dimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…This trend was seen for the four dope concentrations tested: 10, 20, 25 and 30%. At any given PLA content and solution concentration, the viscosity decreased with increasing temperature, as expected because viscosity of polymer solutions is proportional to e 1/ T 21. A polymer concentration of 10% was too low for spinning in the case of all the polymer solutions tested, all being below 0.12 Pas.…”
Section: Resultssupporting
confidence: 62%
“…This trend was seen for the four dope concentrations tested: 10, 20, 25 and 30%. At any given PLA content and solution concentration, the viscosity decreased with increasing temperature, as expected because viscosity of polymer solutions is proportional to e 1/ T 21. A polymer concentration of 10% was too low for spinning in the case of all the polymer solutions tested, all being below 0.12 Pas.…”
Section: Resultssupporting
confidence: 62%
“…The Andrade equation describes the temperature reliance of liquid viscosities . In the present work, a more comprehensive model adopted from the parabolic shape is used in fitting the experimental data. , normalτ = A false[ false( 1 + B 1 true normalγ falsė false) m 1 false] m 1 e C T 1 e D false( 100 W false) where τ/Pa is the shear stress, γ̇/s –1 is the shear rate, and A /Pa, B /s –1 , C /K, D , and m are empirical parameters. T /K is the temperature, and W is the mass fraction of PES in NMP.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, eq 8 for predicting zero shear viscosity can be obtained, where C is the constant. Al-Zahrani and Al-Fariss 44 and Ghasem et al 45 reported that the viscosity of polymer liquid varies exponentially with the concentration as follows where D is a constant and Ø is the content. From the Section 3.4 , the relation between viscosity and solid content follows the principle.…”
Section: Mathematical Model Of Viscositymentioning
confidence: 99%
“…Parameters in eq 11 can be determined by least square nonlinear regression analysis on 160 sets of experimental data. For further comparison, two five-parameter correlations of the viscosity for waxy oils and dimethylacetamide solution proposed by Al-Zahrani 44 and Ghasem 45 were selected. Their correlation equations are as follows …”
Section: Mathematical Model Of Viscositymentioning
confidence: 99%